A New Insight into the Pressure‐Decreasing Mechanism of Hydrophobic Silica Nanoparticles Modified by n‐Propyltrichlorosilane. Issue 4 (6th May 2017) - Zhao, Mingwei; Wang, Shilu; Dai, Caili
Abstract: Hydrophobic silica nanoparticles were prepared for pressure decreasing in water injection through modification of hydrophilic silica nanoparticles by n ‐propyltrichlorosilane. Fourier transform infrared spectroscopy analysis and surface hydroxyl number measurement results certified that the modification was very successful. The core flowing experiment showed that the modified hydrophobic silica nanoparticles have an excellent pressure‐decreasing ability. The contact angles measurement results showed that the core chip changed from strong water wet to neutral wet after treated by the modified silica nanoparticles. In this work, a roughness decreasing mechanism is proposed to explain the pressure‐decreasing mechanism of modified silica nanoparticles. After injection into the core, the modified silica nanoparticles occupied the spaces between the sand grains, forming a discontinuous hydrophobic film on the flowing channel surface. This can not only partially change the wettability of the sand surface, but also decrease the roughness of the core flowing channel, decreasing the critical layer thickness and flowing pressure accordingly.